EveryOne, EveryWhere, EveryWhen: Just water futures for three Living Rivers - R. Quentin Grafton; Anne Poelina; William Brian (Badger) Bates; Matthew Currell; David Doyle; Kirsty Howey; Cecilia Lake; Caroline McFarlane; Anthony McLarty; Nhat-Mai Nguyen; Sam Phelan; Patricia Riley; et al. (Water Security, 2026)

The effects of land use changes on streams and rivers in mediterranean climates - Scott D. Cooper; P. Sam Lake; Sergi Sabater; John M. Melack; John L. Sabo (Hydrobiologia, 2013)

Geometry of biodiversity patterning: assemblages of benthic macroinvertebrates at tributary confluences - Ralph Mac Nally; Elizabeth Wallis; P. Sam Lake (Aquatic Ecology, 2011)

Do tributaries affect loads and fluxes of particulate organic matter, inorganic sediment and wood? Patterns in an upland river basin in south-eastern Australia - Elizabeth Wallis; Ralph Mac Nally; Sam Lake (Hydrobiologia, 2009)

Distribution of anuran amphibians in massively altered landscapes in south‐eastern Australia: effects of climate change in an aridifying region - Ralph Mac Nally; Gregory Horrocks; Hania Lada; P. Sam Lake; James R. Thomson; Andrea C. Taylor (Global Ecology and Biogeography, 2009)
Aim We explored whether the anuran amphibian faunas differed among landscapes that are relatively intact (largely covered in forests and woodlands) and others that are completely converted to agriculture. We also used historical data sets to assess the current condition of the anuran fauna in a region predicted to experience, and experiencing, severe drying and warming. Location Five pairs of landscapes (each of c . 20 km 2 ) – one in each pair being almost completely wooded and the other cleared for agriculture – across a 30,000 km 2 region of northern Victoria, Australia. Methods Sites were repeatedly surveyed in the austral winter–spring breeding seasons of 2006 and 2007, with records collected of numbers of calling males and the presence of egg masses and tadpoles. We characterized the sites using static (e.g. dimensions, surrounding physiognomic characteristics such as tree cover) and labile (e.g. pH, dissolved oxygen) variables. Data were analysed using hierarchical Bayesian models. Results For calling males, landscape type did not affect densities or species richness measures. The availability of a grassy verge around water bodies was an important predictor for most species, but other labile and static variables seemed not to be important. Fewer than half of the species historically known from the region were recorded. There were no important predictors of occurrence of egg masses or tadpoles. Reproduction effectively may have failed over the period, with fewer than one in four sites showing evidence of egg masses or tadpoles. Main conclusions The proportion of sites at which some well‐studied species (e.g. Crinia signifera , Limnodynastes dumerilii ) were recorded has dropped substantially since the 1970s, as have average densities of calling males of Crinia spp. The remnant anuran fauna appears to be dominated by resilient and hardy species with low current diversity. The on‐going (12+ years) drought in these landscapes suggests a bleak long‐term prognosis for the few remaining species of anuran amphibians.

A checklist for ecological management of landscapes for conservation - David Lindenmayer; Richard J. Hobbs; Rebecca Montague‐Drake; Jason Alexandra; Andrew Bennett; Mark Burgman; Peter Cale; Aram Calhoun; Viki Cramer; Peter Cullen; Don Driscoll; Lenore Fahrig; et al. (Ecology Letters, 2008)
The management of landscapes for biological conservation and ecologically sustainable natural resource use are crucial global issues. Research for over two decades has resulted in a large literature, yet there is little consensus on the applicability or even the existence of general principles or broad considerations that could guide landscape conservation. We assess six major themes in the ecology and conservation of landscapes. We identify 13 important issues that need to be considered in developing approaches to landscape conservation. They include recognizing the importance of landscape mosaics (including the integration of terrestrial and aquatic areas), recognizing interactions between vegetation cover and vegetation configuration, using an appropriate landscape conceptual model, maintaining the capacity to recover from disturbance and managing landscapes in an adaptive framework. These considerations are influenced by landscape context, species assemblages and management goals and do not translate directly into on‐the‐ground management guidelines but they should be recognized by researchers and resource managers when developing guidelines for specific cases. Two crucial overarching issues are: (i) a clearly articulated vision for landscape conservation and (ii) quantifiable objectives that offer unambiguous signposts for measuring progress.

Movements of adult female Weddell seals during the winter months - Sam Lake; Harry Burton; Simon Wotherspoon (Polar Biology, 2006)